Microbiome and Its Roles in Gut-Brain Axis - Khing S. Ong; Zack ST. Lim; Boenjamin Setiawan (PT. Kalbe Farma Tbk., 2019)
Among the trillions of microbes that live in our intestinal tract, scientists have found groups of species that play a key role in our health and disease conditions. These microbes harbored on our mucosal and skin surfaces with the bulk of it in the colon of our lower gut system. It is commonly referred to as gut commensal. In this review we summarized briefly our current knowledge of these microbiota or microbiome, and how they work to affect our functions in different organs and systems including our brain and immune system, either directly or indirectly through their metabolites. Technical advances in genetic sequencing such as metagenomic and 16S rRNA (ribosomal RNA) sequencing had greatly facilitate researches on microbiome. Our review will be focused mainly on the roles of microbiome in the gut-brain axis. The use of probiotics and prebiotics for intervention of dysbiosis or altered microbiome will also be discussed.Di antara jutaan mikroba di dalam usus, beberapa kelompok di antaranya dapat berperan dalam kesehatan manusia; secara umum dikelompokkan sebagai gut commensal. Tulisan ini meninjau peranan kelompok tersebut, cara kerjanya dalam memengaruhi metabolisme manusia, termasuk otak dan sistim imun, baik secara langsung maupun dengan perantaraan metabolitnya. Kemajuan teknologi seperti metagenomic dan 16S rRNA (ribosomal RNA) sequencing sangat membantu penelitian mikrobiome. Tulisan ini terutama meninjau peranan mikrobiome pada gut-brain axis; juga akan dibicarakan peranan probiotik dan prebiotik untuk intervensi disbiosis.